Shady solar: understanding barriers and facilitators to residential solar adoption for low- and moderate-income homeowners in New York City - Bansal, Aditi; Dean, Casey; Kahn, Ellie; Sanchez, Daphany Rose; Hernández, Diana (Frontiers in Energy Research, 2024)
Low- and moderate-income (LMI) households face substantial barriers in accessing solar energy despite incentives at the local, state, and federal levels. Notwithstanding the rapid deployment of resources, there is still much to understand and address from a program design and implementation perspective to effectively realize an equitable energy transition. This qualitative study, which draws on interviews with policymakers, implementers, and LMI homeowners, provides novel insights into barriers and facilitators surrounding the inclusive adoption of solar energy. Our findings underscore the substantial differences and frequent misalignments in perspectives among these stakeholders. We find that both implementers and LMI homeowners encounter economic and administrative burdens, though the specific ways these factors hinder solar adoption differ between the groups. We leverage the viewpoints and experiences of policymakers, implementers, and LMI homeowners to guide evidence-based recommendations to overcome the many hurdles that actively impede equitable and inclusive solar adoption.